2015
DOI: 10.1016/j.jstrokecerebrovasdis.2015.06.018
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Circulating Platelets Microparticles and Platelet Parameters in Acute Ischemic Stroke Patients

Abstract: Background Platelet activation and aggregation are critical in the pathogenesis of acute ischemic stroke (AIS). Circulating platelet microparticles (PMPs) and platelet parameters are biological markers of platelet function in AIS patients, however, their associations with stroke subtypes and infarct volume remain unknown. Methods We recruited 112 AIS patients including large artery atherosclerosis (LAA) and small artery occlusion (SAO) subtypes, and 35 controls in this study. Blood samples were collected at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
76
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(80 citation statements)
references
References 49 publications
2
76
1
1
Order By: Relevance
“…This result might be due to the small number of unrecovered patients in this study. MPV and PDW markers have been representing the platelet activation [14][15][16]. The MPV value shows the size of platelets while the PDWvalue is used to evaluate variations in platelet size.…”
Section: Discussionmentioning
confidence: 99%
“…This result might be due to the small number of unrecovered patients in this study. MPV and PDW markers have been representing the platelet activation [14][15][16]. The MPV value shows the size of platelets while the PDWvalue is used to evaluate variations in platelet size.…”
Section: Discussionmentioning
confidence: 99%
“…PMPs participate in a variety of physiological functions, mainly including promotion of blood clotting, endothelial repair, angiogenesis, intercellular signal transduction, and inflammatory responses [8,14,16]. PMPs exist in the blood of normal healthy individuals and different sizes of PMPs have different functions in platelets and ECs [10], and influence many disease processes, including malignant tumor formation, hemolytic disorders, such as thrombotic thrombocytopenic purpura and sickle cell disease, conditional cardiovascular diseases, such as coronary artery disease and stroke, inflammatory diseases, including pregnancy, abortion, and preeclampsia, and the formation of phlebothrombosis [13], atherosclerosis, idiopathic thrombocytopenia purpura, cancer, and rheumatoid arthritis [13].…”
Section: Definition and Physiology Of Platelet-derived Microparticlesmentioning
confidence: 99%
“…Besides, Atherosclerosis is characterized by an increased concentration of CD41 þ and CD61 þ ECs [18]. Meanwhile, it has been demonstrated that PMPs can stimulate aggregation of leukocytes in vitro and express tissue factor (TF) and other cytokines through the pselectin glycoprotein ligand-1 receptor [16]. p-selectin, which is known to promote atherosclerosis via inducing leukocyte recruitment to ECs, is a glycoprotein existing in the membrane of platelet and endothelial cells, also expressed in the membranes of PMPs [23].…”
Section: Pmps and Adhesionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the previous studies conducted on age‐related changes in platelets were conducted on adults of 25–65 years . Furthermore, numerous studies have demonstrated that many diseases, including diabetes, cardiovascular disease, and different physiological states, have an effect on platelet ultrastructure …”
Section: Discussionmentioning
confidence: 99%